2020
DOI: 10.1177/1747954120916073
|View full text |Cite
|
Sign up to set email alerts
|

Australian female athlete perceptions of the challenges associated with training and competing when menstrual symptoms are present

Abstract: Coaches consider various competencies (e.g. conditioning, nutrition, skills and tactics), when planning sessions, though rarely the impact of menstruation on the efficacy of training and competition performance for athletes. Given the impact menstrual symptoms can have on athletes, the management strategies that athletes may use to minimise any potential impact, and the mechanisms that provide barriers to greater coach athlete interaction require investigation and consideration. Therefore, this study aimed to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
67
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 54 publications
(93 citation statements)
references
References 32 publications
8
67
1
Order By: Relevance
“…It is apparent that many athletes believe their performance fluctuates with MC phase; indeed, all included studies reported that MC phase impacted athletes’ perceived performance [ 72 , 73 , 74 , 75 , 76 ]. A large proportion, 50–71% and 49–65%, of participants reported feeling their performance in training and competition, respectively, is impaired in certain MC phases [ 72 , 74 , 76 ]. Perceived strength, speed and power ratings were also altered during certain MC phases [ 75 ].…”
Section: The Impact Of Menstrual Cycle Phase On Perceived Performamentioning
confidence: 99%
See 4 more Smart Citations
“…It is apparent that many athletes believe their performance fluctuates with MC phase; indeed, all included studies reported that MC phase impacted athletes’ perceived performance [ 72 , 73 , 74 , 75 , 76 ]. A large proportion, 50–71% and 49–65%, of participants reported feeling their performance in training and competition, respectively, is impaired in certain MC phases [ 72 , 74 , 76 ]. Perceived strength, speed and power ratings were also altered during certain MC phases [ 75 ].…”
Section: The Impact Of Menstrual Cycle Phase On Perceived Performamentioning
confidence: 99%
“…Athletes most commonly perceived performance to be best in all phases of the MC except the early follicular and late luteal phases [ 76 ] and performance was perceived to be impaired in the early follicular and late luteal phases compared to the rest of the MC [ 72 , 75 , 76 ]. The perceived performance detriment in the early follicular and late luteal phases coincides with the occurrence of menstrual symptoms; a common reason attributed to this perceived performance decline was experiencing fatigue [ 72 ] or lethargy [ 74 ]—which are common menstrual symptoms experienced around menstruation in the general reproductive aged population [ 77 ]—menstrual pain and other menstrual symptoms [ 74 ]. Elite rugby players also cited feeling distracted by their menstrual pain or feeling concerned about flooding during the early follicular phase [ 74 ].…”
Section: The Impact Of Menstrual Cycle Phase On Perceived Performamentioning
confidence: 99%
See 3 more Smart Citations